Waqf Creation and Waqf Assets Value Enhancement: An Exploratory Study in some Organizations in Malaysia - Syed Mohamed Nor, Syed Johan Arif (2013)
Traditionally the role of uplifting economic and social wellbeing of the poor has always been that of the public sector in most countries. This changed towards the end of 20th century with the emergence of Corporate Social Responsibility (CSR) where the private sectors had also joined force to assume similar role. While CSR is a western concept that has been globally recognized today, within the Muslim society there exists similar philanthropic practice which has been around for more than 1000 years called waqf. Waqf originated from an Arabic word of ‘waqafa’ and is defined as “detaining assets that are beneficial and physically lasting, to be given to charity”. In Malaysia, there is an estimated 11,000 hectares of idle waqf land in Malaysia and the cost for development is estimated to be around RM80 billion. Source of funds is a major issue where currently the government is the main source. Further, studies showed that waqf development in Malaysia was hampered by colonialism, poor management, legal issues, and restricted view of waqf itself. This project management thesis will study 10 organizations in Malaysia comprise of public, private and non-profit organization. The study objectives will focus on organization’s motivation, waqf creation and waqf assets value enhancement initiative, and critical success factors. The research methodology will be based on exploratory qualitative non-empirical research with semistructured interview questions. The findings show that for the last decade, there have been an encouraging progress and development with participation from public, private, and non-profit organizations. The selected organization has either managed to create waqf assets and/or further enhance the value of the newly acquired waqf assets or idle waqf land. They have not only contributed toward the improvement of social wellbeing of the Muslim community, but also created economic activities that benefit them and the society. The study also found strong financial support and collaboration are the common critical success factors shared by most organizations understudy, and lack of funding, public awareness, poor waqf framework and lack of expertise as major obstacles and limitations faced by them.